2012
DOI: 10.1037/a0029856
|View full text |Cite
|
Sign up to set email alerts
|

An ideal observer analysis of visual working memory.

Abstract: Limits in visual working memory (VWM) strongly constrain human performance across many tasks. However, the nature of these limits is not well understood. In this paper we develop an ideal observer analysis of human visual working memory, by deriving the expected behavior of an optimally performing, but limited-capacity memory system. This analysis is framed around rate–distortion theory, a branch of information theory that provides optimal bounds on the accuracy of information transmission subject to a fixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
181
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(198 citation statements)
references
References 80 publications
16
181
1
Order By: Relevance
“…Because sequential presentation minimized neural competition at the perceptual level, the similarity effect was unlikely due to differential competition for neural representation during encoding. The similarity advantage was consistent with that shown for colors (Lin & Luck, 2009) and line orientations and lengths (Sims et al, 2012). Thus, high degrees of similarity facilitated memory, even when the stimuli were complex.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Because sequential presentation minimized neural competition at the perceptual level, the similarity effect was unlikely due to differential competition for neural representation during encoding. The similarity advantage was consistent with that shown for colors (Lin & Luck, 2009) and line orientations and lengths (Sims et al, 2012). Thus, high degrees of similarity facilitated memory, even when the stimuli were complex.…”
Section: Discussionsupporting
confidence: 71%
“…Lin and Luck (2009) showed that participants were better at detecting subtle color changes after encoding three highly similar colors (e.g., three shades of red) than three dissimilar colors (e.g., red, green, and yellow). This pattern also emerged in visual working memory for line orientation and length (Sims, Jacobs, & Knill, 2012). Though counterintuitive, the finding fits with several computational models.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…The third motivation for our study was to conduct preliminary tests of a potential variable-resources account of the manner in which VWM declines with the retention interval (e.g., Fougnie, Suchow, & Alvarez, 2012;Sims, Jacobs, & Knill, 2012;van den Berg, Shin, Chou, George, & Ma, 2012). Variable-resources models have been applied successfully to account for the well-known finding that VWM performance declines with increases in memory set size.…”
Section: Sudden Death Versus Extreme Variabilitymentioning
confidence: 99%